Characteristics and Readmission Rates of Tracheostomy Patients Receiving Tailored Discharged Planning: A Retrospective Study - Hanum, Ardani Latifah; Margianti, Tri; Alfajri, Novi Zain; Lestari, Ade Febrina (Jurnal Keperawatan Klinis dan Komunitas (Clinical and Community Nursing Journal), 2026)
Background: Tracheostomy patients often face difficulties after hospital discharge and are at increased risk of readmission. Although discharge planning has proven benefits, studies focusing on tracheostomy patients, particularly those involving case managers, remain limited.Objective: To investigate the characteristics of tracheostomy patients, their readmission rates after individualized discharge planning led by case managers, and 30-day readmission outcomes.Method: A descriptive retrospective study was conducted using electronic health records from 2021 to 2023. Samples were selected through consecutive sampling, including patients who underwent tracheostomy, had been discharged, and received case management services. Data on sociodemographic characteristics, clinical conditions, and 30-day readmission rates were collected and analyzed descriptively using frequency distributions, percentages, medians, and ranges with SPSS 26.Results: Among 50 patients, most were aged 41–65 years (54%) and male (72%). The main indication for tracheostomy was prolonged mechanical ventilation (72%), with a median length of stay of 40,5 days. About 54% were discharged with a tracheostomy tube and other invasive devices, including nasogastric tubes (62%) and urinary catheters (28%). A total of 94% of patients had no readmission within 30 days post-discharge.Conclusion: Tracheostomy patients have complex conditions requiring continued home care; however, readmission rates are low. Case management and individualized discharge planning may help prevent readmissions in high-risk patients.INTISARILatar belakang: Pasien trakeostomi sering menghadapi kesulitan setelah pulang dari rumah sakit dan memiliki risiko tinggi untuk mengalami readmisi. Meskipun manfaat perencanaan pulang telah terbukti, studi yang berfokus pada pasien trakeostomi, khususnya yang melibatkan manajer kasus, masih terbatas.Tujuan: Menyelidiki karakteristik pasien trakeostomi, tingkat readmisi setelah mendapatkan perencanaan pulang individual yang dipimpin oleh manajer kasus, serta luaran readmisi dalam 30 hari.Metode: Penelitian deskriptif retrospektif dilakukan menggunakan data rekam medis elektronik dari tahun 2021 hingga 2023. Sampel dipilih melalui consecutive sampling, meliputi pasien yang menjalani trakeostomi, telah dipulangkan, dan menerima layanan manajemen kasus. Data mengenai karakteristik sosiodemografi, kondisi klinis, serta tingkat readmisi 30 hari dikumpulkan dan dianalisis secara deskriptif dalam bentuk distribusi frekuensi, persentase, median, dan rentang menggunakan SPSS 26.Hasil: Dari 50 pasien, sebagian besar berusia 41–65 tahun (54%) dan berjenis kelamin laki-laki (72%). Indikasi utama trakeostomi adalah ventilasi mekanik berkepanjangan (72%), dengan median lama rawat 40,5 hari. Sekitar 54% pasien dipulangkan dengan kanul trakeostomi serta alat invasif lain, seperti selang nasogastrik (62%) dan kateter urine (28%). Sebanyak 94% pasien tidak mengalami readmisi dalam 30 hari setelah pulang.Simpulan: Pasien trakeostomi memiliki kondisi yang kompleks dan memerlukan perawatan lanjutan di rumah, namun, tingkat readmisi relatif rendah. Manajemen kasus dan perencanaan pulang individual dapat membantu mencegah readmisi pada pasien berisiko tinggi.